Domingos José Martins: a invenção de um herói para os capixabas no Instituto Histórico e Geográfico do Espírito Santo - Bigossi, Bruna Breda (2018)
Domingos José Martins was one of the leaders of the Pernambucan Revolution, that took place in the province of Pernambuco, Brazil, in 1817. In 1916, year that the Instituto Histórico e Geográfico do Espírito Santo (IHGES) (Historical and Geographical Institute of Espirito Santo) was founded, Domingos Martins was granted the status of a capixaba (from Espirito Santo) hero and patron of this institution in a moment of the Brazilian History when the election of local myths and symbols were important to legitimate the republican regime. Given that, this dissertation aims to trace the Domingos Martin’s depiction as a hero throughout the nineteenth and early twentieth century in the disciplinary historiography and on the IHGES and on its review. It is important, on this work, to point out how some historic characters’ images can be manipulated over the time to justify or reinforce certain ideas of restricted social groups and in order to provide lessons or society models, as articulated by José Murilo de Carvalho and Armelle Enders. To back up this hypotheses, Martins’ case is exemplar as it gathers the characteristics that served to represent and at the same time project a glorious and republican capixaba past – in this sense, this work relates itself to the critical turn in the capixaba historiography.